The influence of the COVID-19 pandemic on videolaryngoscopy: a cross-sectional before-and-after survey - (:unkn) unknown (My University, 2023)
Background: Guidelines and consensus statements recommend the use of videolaryngoscopes (VLs) in airway management of patients with COVID19. However, there is a lack of knowledge about which types of videolaryngoscopes are used, differences of use between countries, and how the COVID19 pandemic influenced their use. The primary aim of this beforeandafter crosssectional survey study was to assess the frequency of the use of videolaryngoscopy in the operation theatres in different countries. Also, the preferred characteristics of videolaryngoscopes were assessed. Methods: With Ethics Committee approval, a questionnaire was distributed among anaesthesiologists through the European Airway Management Society’s network in 2019 before and in 2021 during the COVID19 pandemic. Responses to the questions were analysed and presented as descriptive statistics. Results: We reached out to 791 anaesthesiologists; 155 (19.5%) returned the first questionnaire, and 91 (11.5%) returned the second survey. Videolaryngoscopes were used in 24.1% of cases before COVID19 and in 43.1% after the pandemic (P < 0.001). We revealed that the availability of videolaryngoscopes increased to 100% in all centres during the pandemic. Routine use of videolaryngoscopes in all cases increased from 12.5% to 38.9%. The type of videolaryngoscope and the blade preference did not change during this period (P= 1.000). Conclusions: This survey reflects that the COVID19 pandemic significantly increased the availability and use of videolaryngoscopes in operating theatres, and that more anaesthesiologists now use them routinely in all cases. The preferred type of VL or blade did not change during the pandemic.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Yoğun Bakım; Cerrahi Tıp Bilimleri; Anesteziyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Intensive Care; Surgery Medicine Sciences; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ANESTEZİYOLOJİ; YOĞUN BAKIM; Clinical Medicine (MED); CLINICAL MEDICINE; ANESTHESIOLOGY; CRITICAL CARE MEDICINE; Yoğun Bakım Tıbbı; Anesteziyoloji ve Ağrı Tıbbı; Critical Care and Intensive Care Medicine; Anesthesiology and Pain Medicine; airway management; COVID19; equipment; intubation; videolaryngoscope